Netralitas Kepolisian Republik Indonesia Pada Penyelenggaraan Pemilihan Umum - Anib Bastian; Rustam Hs. Akili; Yusrianto Kadir (Pusat Riset dan Inovasi Nasional, 2024)
The neutrality of the Indonesian National Police (POLRI) in holding general elections is an important prerequisite for the integrity and success of the democratic process in Indonesia. In this context, the neutrality of the National Police reflects its ability to carry out state duties without taking sides with certain political interests. The National Police has a crucial role in ensuring security, order and justice during the elections, including securing voting locations, enforcing the law against election violations, and providing a sense of security to the public. However, maintaining the neutrality of the National Police is not an easy task. The National Police is faced with various challenges, such as political pressure, intervention by certain interests, and threats to the security of its personnel. Nevertheless, the National Police has developed various strategies to overcome these challenges and maintain its neutrality during the elections.